2019
DOI: 10.1007/s10964-019-01096-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Identity Formation: Linking the Narrative and the Dual-Cycle Approach

Abstract: The narrative and dual-cycle approach conceptualize and operationalize adolescents' identity formation in different ways. While the narrative approach focuses on the construction of an autobiographical life story, the dual-cycle approach focuses on the formation of identity commitments. Although these approaches have different emphases, they are conceptually complementary. Yet, their empirical links and distinctions have only scarcely been investigated. Empirical knowledge on these links in adolescence and acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 54 publications
(99 reference statements)
2
51
1
3
Order By: Relevance
“…Future research in this area might also consider assessing identity among individuals at CHR through contemporary research frameworks, including the narrative approach (i.e., developing a coherent life story), the dual-cycle approach (i.e., developing and evaluating identity commitments in breadth and depth), and the certaintyuncertainty model (i.e., reevaluating past commitments, such as those influenced by caregivers' beliefs; Schwartz et al, 2005Schwartz et al, , 2013van Doeselaar, McLean, et al, 2019). Specific to psychosis, future research should also consider how identity changes in psychosis can result from many different factors (symptoms, cognitive and social functioning, stigma, understanding of psychosis, meaning-making, personal growth, and positive changes; Conneely et al, 2020;Friesen et al, 2021).…”
Section: Future Researchmentioning
confidence: 99%
“…Future research in this area might also consider assessing identity among individuals at CHR through contemporary research frameworks, including the narrative approach (i.e., developing a coherent life story), the dual-cycle approach (i.e., developing and evaluating identity commitments in breadth and depth), and the certaintyuncertainty model (i.e., reevaluating past commitments, such as those influenced by caregivers' beliefs; Schwartz et al, 2005Schwartz et al, , 2013van Doeselaar, McLean, et al, 2019). Specific to psychosis, future research should also consider how identity changes in psychosis can result from many different factors (symptoms, cognitive and social functioning, stigma, understanding of psychosis, meaning-making, personal growth, and positive changes; Conneely et al, 2020;Friesen et al, 2021).…”
Section: Future Researchmentioning
confidence: 99%
“…El abordaje de las teorías narrativas comparte puntos en común con la perspectiva ericksoniana, planteando a la identidad como un concepto sistémico-narrativo, sociallingüísticamente construido. Desde este abordaje y, a través de las narraciones de las historias de vida, los sujetos buscan integrar su historia personal y generar un sentimiento de continuidad y unidad de sí mismos (Van Doeselaar et al, 2020). Desde esta perspectiva, los sujetos aprenden sobre sí mismos a través de las historias personales que cuentan a los demás y a través de las historias que los demás cuentan sobre ellos .…”
Section: Adolescencia Identidad E Identidad Narrativaunclassified
“…Granic et al (2020) suggested that the dynamics of the needs for agency and communion shift during adolescence and that this shift may be reflected in the relative prominence on agency versus communion themes in a narrative identity. Specifically, as adolescents start to engage in self-exploration and gain better insight into their own interests and values, a predominance of communion themes may give way to a predominance of agency themes (see Van Doeselaar et al, 2020, for some indirect support for this). Toward the end of adolescent identity development, when the needs for agency and communion become more balanced, agency and communion themes may become relatively equalized and united in a narrative identity.…”
Section: The Construction Of a Coherent Life Story In Adolescencementioning
confidence: 99%